Pengaruh Waktu Pengeringan Apusan Epitel Mukosa Oral terhadap Kualitas Pewarnaan Diff-Quik - Putra, Suseno Adi; Sobalely, Juneth Jennifer; Mahundingan, Fitri Claudia Agathis; Kindangen, Gabriella Aurel; Lusiana, Diana Intan Gabriella; Setyoningrum, Fransisca Probo (Lembaga Teewan Journal Solutions, 2026)
Oral exfoliative cytology is a non-invasive diagnostic method widely used to evaluate morphological changes in oral mucosal epithelial cells. The quality of cytological preparations is influenced by several pre-analytical factors, including the air-drying time before Diff-Quik staining. This study aimed to determine the effect of different air-drying times on the staining quality of oral mucosal epithelial smears using the Diff-Quik method. A descriptive experimental design was employed with four air-drying time groups: 0, 5, 10, and 15 minutes. A total of 24 buccal smear preparations obtained from six healthy volunteers were evaluated. Slide quality was assessed based on nuclear clarity, cytoplasmic characteristics, and nuclear-cytoplasmic contrast using an objective scoring system. The results showed that all treatment groups achieved total scores ranging from 7 to 9, indicating good staining quality. The 0- and 5-minute air-drying groups produced the most optimal staining results, demonstrating clearer nuclear and cytoplasmic details, whereas the 10- and 15-minute groups exhibited a slight reduction in staining contrast in several preparations without significant morphological alterations. In conclusion, air-drying times of up to 15 minutes still produced cytological preparations with good staining quality, although 0–5 minutes provided the most optimal Diff-Quik staining results.